2015
DOI: 10.1103/physrevb.91.214508
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting spin-valve effect and triplet superconductivity inCoOx/Fe1/Cu/Fe2/Cu/Pbmultilayer

Abstract: We report magnetic and superconducting properties of the modified spin valve system CoOx/Fe1/Cu/Fe2/Cu/Pb. Introduction of a Cu interlayer between Fe2 and Pb layers prevents material interdiffusion process, increases the Fe2/Pb interface transparency, stabilizes and enhances properties of the system. This allowed us to perform a comprehensive study of such heterostructures and to present theoretical description of the superconducting spin valve effect and of the manifestation of the long-range triplet componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
1
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 59 publications
(73 reference statements)
7
38
1
5
Order By: Relevance
“…Indeed, recent calculations have shown [42] that not only the "direct switching" ( ) [42], which can be most spectacularly detected as a reentrant behavior of superconductivity as a function of the angle between magnetic moments of the F1 and F2 ferromagnetic layers. It has been shown that superconducting T c for the F1/N/F2/S structure, calculated with physical parameters derived from the experiments described above, keeps all features predicted in [42] for the simplified model, and the triplet component was detected in F1/N/F2/S multilayer structure [44][45][46][47][48] opening the perspectives for the triplet spin-valve design for superconducting electronics [49,50]. One can see that the functionality of the superconductor/ferromagnet layered nanostructures can be successfully utilized to build a novel base elements for superconducting electronics development.…”
Section: Other Possible Design Of Superconducting Spin Valve -"Triplementioning
confidence: 63%
See 1 more Smart Citation
“…Indeed, recent calculations have shown [42] that not only the "direct switching" ( ) [42], which can be most spectacularly detected as a reentrant behavior of superconductivity as a function of the angle between magnetic moments of the F1 and F2 ferromagnetic layers. It has been shown that superconducting T c for the F1/N/F2/S structure, calculated with physical parameters derived from the experiments described above, keeps all features predicted in [42] for the simplified model, and the triplet component was detected in F1/N/F2/S multilayer structure [44][45][46][47][48] opening the perspectives for the triplet spin-valve design for superconducting electronics [49,50]. One can see that the functionality of the superconductor/ferromagnet layered nanostructures can be successfully utilized to build a novel base elements for superconducting electronics development.…”
Section: Other Possible Design Of Superconducting Spin Valve -"Triplementioning
confidence: 63%
“…According to Ref. 20, l F ≈ 4.4 nm for a Cu 47 Ni 53 alloy with resistivity ρ F = 57 μΩ·cm (bulk material, T = 10 K). Assuming that the product 〈ρ F l F 〉 ≈ 2.5·10 -5 μΩ·cm 2 remains unchanged upon adding impurities [21] one gets l F ~ 10 nm for our Cu 41 Ni 59 alloy using the data for the low-temperature resistivity from Ref.…”
Section: Oscillations Of Superconducting T C In S/f Bilayersmentioning
confidence: 97%
“…For the CoO x /Fe1/Cu/Fe2/Cu/Pb structure, the superconducting spin-valve effect ∆T c vanishes in the range of thicknesses d Fe2 ≈0.8-1.0 nm [17,20]. From the analysis of the data on the dependence T c (d Py ), it was concluded that the depth of penetration of the Cooper pairs into the permalloy layer is two times greater than the value obtained for iron.…”
Section: Resultsmentioning
confidence: 84%
“…In all previous studies of our group (see [10,[17][18][19][20]), the experimental data on the critical temperature T c were compared with the parameter of the theory W, which determines the degree of suppression of superconductivity by the ferromagnetic layer (see [7]). The effective boundary condition for the real component of the anomalous Green's function can be written as…”
Section: Discussion Of Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation